GAMBARAN PENGETAHUAN IBU TENTANG ASI EKSLUSIF - Mastiur Vita Insani Silalahi; Tri Puspa Kusumaningsih (Jurnal Komunikasi Kesehatan, 2022)
A balanced and natural composition that is in accordance with the development and growth needs of the baby makes exclusive breastfeeding an ideal source of nutrition for babies. Exclusive breastfeeding is of very high quality, easy to obtain and cheap, breastfeeding can be done as often as possible for babies, therefore breast milk is also the most perfect and best nutrition for babies. The purpose of the study was to describe the mother's knowledge about exclusive breastfeeding in infants aged 0-6 months. The type of research used is a descriptive survey with a cross sectional approach. The population of this research is mothers who are breastfeeding their babies aged 0-6 months in the working area of the Banyuurip Health Center, the sampling technique uses total sampling with a total sample of 30 respondents. The data collection tool uses a questionnaire. Data analysis used univariate analysis. The results of the study were that most of the mothers' level of knowledge about exclusive breastfeeding was sufficient.